A Process Study of Evolving Paradoxes and Cross-Sector Goals: A Partnership to Accelerate Global Sustainability - Williams, Amanda; Parker, John N.; Kennedy, Steve; Whiteman, Gail (Journal of Management, 2026)
Cross-sector partnerships formed to address societal challenges are widely advocated and increasingly common. Joint goal setting is an essential phase in the collaborative process that can determine the course of a partnership. Yet, little is known about how cross-sector goals change and evolve because goal alignment between partners is often taken for granted. In this article, we qualitatively investigate a case of goal setting within a high-profile partnership across the academic and business sectors called Action2020, which aimed at accelerating global corporate sustainability action based on the planetary boundaries framework. We find that cross-sector goal setting is an iterative, multiphase process complicated by deep-seated sectoral differences that trigger paradoxes and conflict. Our main contribution is a process model of cross-sector goal setting comprising three phases: coalescing, protecting, and reconciling sectoral interests. Our model offers three unique insights that advance the cross-sector paradox literature: Altering the cross-sector goal can harness new opportunities of key turning points in the collaboration, shifting the opposing poles of paradoxes may be a necessary management approach to overcome collaborative barriers, and intermediaries may dampen the ambition of collaborative goals in order to temper paradoxes. We also contribute to the corporate sustainability literature and discuss the implications of moving from organization-centric to systems-based sustainability targets.